GEL PROPERTIES OF GELATIN FROM CLOWN FEATHERBACK (CHITALA ORNATA) SKIN: EFFECT OF SWELLING TIME - Kittiphattanabawon, Phanat; Benjakul, Soottawat (Emirates Journal of Food and Agriculture, 2017)
Characteristic and gel properties of gelatin from the skin of clown featherback (Chitala ornata J. E. Gray, 1831) as affected by different swelling time (0, 15, 30, 60, 120 and 240 min) were investigated. The highest and lowest recoveries of gelatin were found when the gelatin extracted from skin swollen for 15 and 30 min (80.98-81.52%) and 240 min (40.47%), respectively. Gelatin extracted from swollen skin had -, - and -chains as the major component, while their major components gelatin extracted from non-swollen skin were degrade into smaller peptides. The swelling time did not affect the gel strength (330-342 g), gelling temperature (23.29-23.76 C) and gelling time (12.03-12.23 min). In contrast, gelatin extracted from non-swollen skin showed poor recovery (9.80%), gel strength (82 g), gelling temperature (12.8 C) and cannot be set at 25 C within 60 min. Therefore, the skin should be swollen with 0.1 M acetic acid for 15 min before extraction.